Clinical view of the ineffectiveness of IVF problem with endometrial receptivity - П. Н. Веропотвелян; И. С. Цехмистренко (Publishing House TRILIST, 2017)
Objective: To review the literature for studying the mechanisms of influence of superovulation on the receptivity of the endometrium in vitro fertilization (IVF), which is largely due not only to the quality of the embryo, but with the condition of the endometrium, its maturity and readiness for implantation. Given the fact that with each subsequent attempt likelihood of a positive outcome of IVF decreases endometrial maturation process optimization, training of "implantation window", as well as support the development of pregnancy in the early stages of its development represents an important aspect of improving the effectiveness of ART. Successful implantation endometrium maturation, including the formation and readiness pinopody embryo must be accurately synchronized in time and space (an "implantation window"), which corresponds to 19-21 days menstrual cycle. Materials and methods: In the course of acquaintance with the publication presents the morphological characteristics of the endometrium in stimulated cycles. Presents current views on endometrial receptivity and the molecular mechanisms regulation of implantation. Results: The features of the expression of estrogen and progesterone receptors, as well as other markers of endometrial receptivity (pinopodii, leukemia inhibitory factor, integrins) in natural and stimulated cycles. Patients with a history of failure of implantation prior to IVF ART program is necessary to analyze all inducers affecting the endometrium, endometrial morphological landscape, E2 receptor expression and progesterone pinopodii, integrins, molecular and genetic aspects of the endometrium in stimulated cycles. Conclusion: The analysis of numerous publications showing an adverse effect on superovulation endometrial receptivity in assisted reproduction programs. Undetermined noninvasive markers to assess the receptivity of the endometrium, including in stimulated cycles. Not evaluated linically significant endometrial threshold level of progesterone on the day of ovulation trigger and insufficiently studied the possible mechanisms of the effect of a premature increase of progesterone on the outcomes of IVF. Therefore, further study and development of the best approaches for the prevention and correction of the negative impact of ovarian stimulation function on the endometrium in assisted reproduction programs.